Inline electrochemical reduction of NISTmAb for middle-up subunit liquid chromatography-mass spectrometry analysis. Issue 21 (29th September 2021) - Morgan, Tomos E.; Jakes, Craig; Brouwer, Hendrik-Jan; Millán-Martín, Silvia; Chervet, Jean-Pierre; Cook, Ken; Carillo, Sara; Bones, Jonathan
Abstract : Complete inline reduction of NISTmAb disulfide bonds using an electrochemical cell coupled to LC-MS analysis, reduction is carried out without the use of traditional reducing agents or enzymes. Abstract : Disulfide bond reduction within antibody mass spectrometry workflows is typically carried out using chemical reducing agents to produce antibody subunits for middle-down and middle-up analysis. In this contribution we offer an online electrochemical reduction method for the reduction of antibodies coupled with liquid chromatography (LC) and mass spectrometry (MS), reducing the disulfide bonds present in the antibody without the need for chemical reducing agents. An electrochemical cell placed before the analytical column and mass spectrometer facilitated complete reduction of NISTmAb inter- and intrachain disulfide bonds. Reduction and analysis were carried out under optimal solvent conditions using a trapping column and switching valve to facilitate solvent exchange during analysis. The level of reduction was shown to be affected by electrochemical potential, temperature and solvent organic content, but with optimization, complete disulfide bond cleavage was achieved. The use of an inline electrochemical cell offers a simple, rapid, workflow solution for liquid chromatography mass spectrometry analysis of antibody subunits.